The relationship between thermal spatial variability and mean temperature alters movement and population dynamics. Issue 9 (29th September 2022) - Schuman, Isaac J.; Meier, Hannah S.; Layden, Tamara J.; Fey, Samuel B.
Abstract: The importance of spatial and temporal environmental variation in shaping ecosystem dynamics is well appreciated, yet the ecological consequences of dynamic spatial variability, that is, the temporal patterning of spatial variation, remain unresolved. Here, we experimentally generate temporally fluctuating thermal environments that have either a negative, positive, or neutral relationship between the mean spatial environmental temperature and the degree of thermal spatial heterogeneity. We test the hypothesis that the timing of spatial variation relative to diel temperature cycles can meaningfully alter movement patterns and population dynamics, using the motile green algae Chlamydomonas reinhardtii . Our results indicate that C. reinhardtii individuals growing in environments with positive relationships between spatial variability and mean temperature show reduced population growth rates, more directed movement as indicated by a reduced turning angle, and decreased negative thermotaxis over time, relative to those growing in environments with a negative relationship between spatial variability and mean temperature. We additionally document substantial regional variation in the dynamics of natural spatial variability by collecting summer water temperature measurements from five ponds in the Mount Saint Helens watershed, WA, USA. Our results collectively suggest that the dynamics of spatial variation are an underappreciated but salient feature within the broader interwoven fabric of spatiotemporal variation.